Correlation Between Blood Glucose Variability and Early Therapeutic Effects After Intravenous Thrombolysis With Alteplase and Levels of Serum Inflammatory Factors in Patients With Acute Ischemic Stroke - Cai, Yun; Zhang, Hongtao; Li, Qiang; Zhang, Peilan (Frontiers in Neurology, 2022)
Objective To investigate the effects of blood glucose variability on early therapeutic effects after intravenous thrombolysis with alteplase and the levels of serum inflammatory factors in patients with acute ischemic stroke. Methods We enrolled patients who received intravenous thrombolysis within 4.5 hours of the onset of symptoms. Clinical data, including the NIHSS, glycosylated hemoglobin, mean blood glucose, standard deviation of blood glucose, mean amplitude of glycemic excursion, mean variation coefficient of blood glucose, IL-6, MMP-9, TNF-α, and hs-CRP levels, were compared between the improvement group and the non-improvement group. Relevant factors for early neurological improvement after thrombolysis with alteplase were analyzed by using multivariate logistic regression models. A Pearson linear correlation analysis was also performed on blood glucose variation and inflammatory factor levels within the two groups. Results A total of 146 patients were included, 63 of which had early symptom improvement (43.15%). The diabetes ratio, atrial fibrillation ratio, baseline NHISS score, random blood glucose at admission, and glycosylated hemoglobin of patients in the improvement group were significantly lower than those in the non-improvement group(P＜0.05). The mean blood glucose, standard deviation of blood glucose, mean amplitude of glycemic excursion, and mean blood glucose variation coefficients of patients in the improvement group were significantly lower than those in the non-improvement group(P＜0.05). Serum inflammatory factor levels were significantly lower in patients in the improvement group(P＜0.05). Multivariate logistic regression analysis showed that baseline NIHSS scores (OR=1.28, 95% CI=1.05~1.62, P=0.02), glycosylated hemoglobin scores (OR=2.57, 95% CI=1.78~3.98, P=0.0005), diabetes (OR=13.10, 95% CI=1.63~131.45, P=0.021), the mean amplitude of glycemic excursion (OR=2.98，95% CI=1.92~5.00, P<0.0001), and the mean variation coefficient of blood glucose (OR=1.40，95% CI=1.26~1.60，P=0.0078) were significantly correlated with early symptom improvement after thrombolysis. Pearson linear correlation analysis showed that the standard deviation of blood glucose, mean amplitude of glycemic excursion, and the mean variation coefficient of blood glucose were significantly positively correlated with IL-6, MMP-9, TNF-α and hs-CRP levels (P<0.01). Conclusions Blood glucose variability is correlated with early neurological improvement after intravenous thrombolysis with alteplase in AIS patients. With the increase of blood glucose fluctuation range, the inflammatory response is enhanced, which affects the prognosis of patients.